Effect of Dopant Loading on the Structural and Catalytic Properties of Mn-Doped SrTiO3 Catalysts for Catalytic Soot Combustion - Suárez Vázquez, Santiago Iván; Cruz López, Arquímedes; Molina Guerrero, Carlos; Sánchez Vázquez, Astrid Iriana; Macías Sotelo, Carlos (2018)
Abstract: Soot particles have been associated with respiratory diseases and cancer. To decrease these emissions, perovskite-mixed oxides have been proposed due to their thermal stability and redox surfaceproperties. Inthiswork,SrTiO3 dopedwithdifferentamountsofMnweresynthesizedbythe hydrothermalmethodandtestedforsootcombustion. ResultsshowthatatlowMncontent,structural distortion,andhigherOads/Olat ratiowereobservedwhichwasattributedtothehighcontentofMn3+ inTisites. Ontheotherhand,increasingtheMncontentledtosurfacesegregationofmanganeseoxide. All synthesized catalysts showed mesopores in the range of 32–47 nm. In the catalytic combustion of soot, the samples synthesized in this work lowered the combustion temperature by more than 100◦C compared with the uncatalyzed reaction. The sample doped with 1 wt % of Mn showed the best catalytic activity. The activation energy of these samples was also calculated, and the order of decreasingactivationenergyisasfollows: uncatalyzed>Mn0>Mn8>Mn4>Mn1. Thebestcatalytic activityforMn1wasattributedtoitsphysicochemicalpropertiesandthemobilityoftheoxygenfrom the bulk to the surface at temperatures higher than 500◦C. Keywords: activation energy; hydrothermal synthesis; catalytic combustion; soot; perovskite